Kontribusi Sektor Pertanian terhadap Produk Domestik Regional Bruto (PDRB) di Kabupaten Tabalong - Azwar Saihani; Lina Heldayani (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
This study aims to determine the basis and non-basis, the contribution and growth of each agricultural subsector to the GRDP in Tabalong Regency from 2013 to 2017. The analytical method used is the Location Quotient analysis, contributions, and shift-share. The data used are Tabalong Regency GRDP data from 2013 to 2017 based on constant prices. The time of the study starts from June 2018 until August 2019. The results of the study based on the Location Quotient analysis show that the subsector that is the base subsector is the plantation subsector while the other subsectors such as food crops, horticulture, and fisheries are the non-basis subsector in Tabalong Regency. The results of the Contribution analysis show that of the five agricultural subsectors in Tabalong District, the highest contribution to the agricultural sector was the plantation subsector in the last five years by 47.87%. The results of the Shift Share analysis show the growth of each agricultural sub-sector in the economy of the Tabalong district is different as seen from the proportional growth of the food crops, livestock and fisheries sub-sectors experiencing rapid growth while the horticulture and plantation sub-sectors experienced slow growth. which is not competitive or less competitive with other regions in South Kalimantan Province.This study aims to determine the basis and non-basis, the contribution and growth of each agricultural subsector to the GRDP in Tabalong Regency from 2013 to 2017. The analytical method used is the Location Quotient analysis, contributions, and shift-share. The data used are Tabalong Regency GRDP data from 2013 to 2017 based on constant prices. The time of the study starts from June 2018 until August 2019. The results of the study based on the Location Quotient analysis show that the subsector that is the base subsector is the plantation subsector while the other subsectors such as food crops, horticulture, and fisheries are the non-basis subsector in Tabalong Regency. The results of the Contribution analysis show that of the five agricultural subsectors in Tabalong District, the highest contribution to the agricultural sector was the plantation subsector in the last five years by 47.87%. The results of the Shift Share analysis show the growth of each agricultural sub-sector in the economy of the Tabalong district is different as seen from the proportional growth of the food crops, livestock and fisheries sub-sectors experiencing rapid growth while the horticulture and plantation sub-sectors experienced slow growth. which is not competitive or less competitive with other regions in South Kalimantan Province.